Case Report: A giant myopericytoma involving the occipital region of the scalp - a rare entity - Munakomi, Sunil (F1000Res, 2016)
Herein we report a rare case of a giant myopericytoma presenting in a 16-year-old girl as a slowly progressive swelling involving the scalp in the occipital region. It was managed by complete excision. Histological examination of the lesion revealed  spindle-shaped cells forming characteristic rosettes around the blood vessels, and positive staining with smooth muscle actin.